Transcriptional refractoriness is dependent on core promoter architecture - Cesbron, François; Oehler, Michael; Ha, Nati; Sancar, Gencer; Brunner, Michael (Nature Communications, 2015)
Genes are often transcribed in random bursts followed by long periods of inactivity. Here we employ the light-activatable white collar complex (WCC) of Neurospora to study the transcriptional bursting with a population approach. Activation of WCC by a light pulse triggers a synchronized wave of transcription from the frequency promoter followed by an extended period (∼1 h) during which the promoter is refractory towards restimulation. When challenged by a second light pulse, the newly activated WCC binds to refractory promoters and has the potential to recruit RNA polymerase II (Pol II). However, accumulation of Pol II and phosphorylation of its C-terminal domain repeats at serine 5 are impaired. Our results suggest that refractory promoters carry a physical memory of their recent transcription history. Genome-wide analysis of light-induced transcription suggests that refractoriness is rather widespread and a property of promoter architecture.